ARBITRATION AS A MECHANISM TO RESOLVE ISLAMIC BANKING DISPUTES IN MALAYSIA: CHALLENGES AND DRAWBACKS (UUM Journal of Legal Studies, 2019)
Malaysia has shown tremendous progress in the arena of Islamic banking and the finance industry, and has become an essential Islamic financial hub within the region. The comprehensive legal framework consisting of legislation and dispute resolution mechanisms have been crucial elements that ensured the robust development of the industry. The court system and arbitration are two significant platforms for the settlement of Islamic banking disputes that are brought before them. However, the court system has been widely favoured compared to the arbitration, even though both approaches have almost identical roles. Therefore, one question arises; why is arbitration less preferred compared to the court system? By using legal research methods, this article seeks to analyse the challenges and drawbacks that faces the current arbitration framework when dealing with Islamic banking disputes. This study suggests that the Malaysian arbitration framework faces several challenges such as, issues regarding high-cost, high-formality, less-speed, and the uncertainties when referring any Shariah matters to the Shariah Advisory Council. This article suggests that some improvements should be made by the relevant authorities and establish the necessary statutory amendments to strengthen the role of arbitration in Malaysia as a complementary forum to the court system in settling Islamic financial disputes.